Peranan Dinas Koperasi Dan Usaha Mikro Sidoarjo Dalam Pemberdayaan UMKM Coffe Shop Di Kecamatan Sidoarjo - Kharisma Dessy Suryaningrum; Tri Prasetijowati; Ismail (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
The role of the Department of Cooperatives and Micro Enterprises in empowering Coffee Shop MSMEs is very influential, making the government take part in empowerment. The aim of this research is to analyze the role of the Sidoarjo Cooperatives and Micro Enterprises Service, analyze the factors that influence the empowerment of Coffee Shop MSMEs in Sidoarjo and analyze the efforts of the Cooperatives and Micro Enterprises Service in empowering Coffee Shop MSMEs. This research uses qualitative methods. The results of this research are that the role of the Sidoarjo Cooperatives and Micro Enterprises Service is not good enough in terms of capital and innovation in empowering Coffee Shop MSMEs. However, business actors are still not utilizing the capital facilities provided in terms of access to capital. The advice given is to carry out supervision by the Department during this period in the continuity of empowerment which is carried out so that there is continuity for MSME actors, especially in the Coffee Shop MSMEs in Sidoarjo Regency, providing guidance to MSME actors to always be optimistic in developing their businesses in order to create advanced and independent MSMEs so that more employment is being absorbed.The role of the Department of Cooperatives and Micro Enterprises in empowering Coffee Shop MSMEs is very influential, making the government take part in empowerment. The aim of this research is to analyze the role of the Sidoarjo Cooperatives and Micro Enterprises Service, analyze the factors that influence the empowerment of Coffee Shop MSMEs in Sidoarjo and analyze the efforts of the Cooperatives and Micro Enterprises Service in empowering Coffee Shop MSMEs. This research uses qualitative methods. The results of this research are that the role of the Sidoarjo Cooperatives and Micro Enterprises Service is not good enough in terms of capital and innovation in empowering Coffee Shop MSMEs. However, business actors are still not utilizing the capital facilities provided in terms of access to capital. The advice given is to carry out supervision by the Department during this period in the continuity of empowerment which is carried out so that there is continuity for MSME actors, especially in the Coffee Shop MSMEs in Sidoarjo Regency, providing guidance to MSME actors to always be optimistic in developing their businesses in order to create advanced and independent MSMEs so that more employment is being absorbed.